Immunity against measles, mumps, rubella, varicella, diphtheria, tetanus, polio, hepatitis A and hepatitis B among adult asylum seekers in the Netherlands, 2016. Issue 12 (14th March 2018) - Freidl, Gudrun S.; Tostmann, Alma; Curvers, Moud; Ruijs, Wilhelmina L.M.; Smits, Gaby; Schepp, Rutger; Duizer, Erwin; Boland, Greet; de Melker, Hester; van der Klis, Fiona R.M.; Hautvast, Jeannine L.A.; Veldhuijzen, Irene K.
Highlights: Seroprotection levels against VPDs among adult asylum seekers are generally high. Measles seroprotection was below the 95% elimination threshold except for Eritreans. Results are useful to guide vaccination policies for adult asylum seekers. Abstract: Asylum seekers are a vulnerable population for contracting infectious diseases. Outbreaks occur among children and adults. In the Netherlands, asylum seeker children are offered vaccination according to the National Immunization Program. Little is known about protection against vaccine-preventable diseases (VPD) in adult asylum seekers. In this 2016 study, we assessed the immunity of adult asylum seekers against nine VPD to identify groups that might benefit from additional vaccinations. We invited asylum seekers from Syria, Iran, Iraq, Afghanistan, Eritrea and Ethiopia to participate in a serosurvey. Participants provided informed consent and a blood sample, and completed a questionnaire. We measured prevalence of protective antibodies to measles, mumps, rubella, varicella, diphtheria, tetanus, polio type 1–3 and hepatitis A and B, stratified them by country of origin and age groups. The median age of the 622 participants was 28 years (interquartile range: 23–35), 81% were male and 48% originated from Syria. Overall, seroprotection was 88% for measles (range between countries: 83–93%), 91% for mumps (81–95%), 94% for rubella (84–98%), 96% for varicella (92–98%), 82% for diphtheria (65–88%), 98% for tetanus (86–100%), 91% (88–94%) for polio type 1, 95% (90–98%) for polio type 2, 82% (76–86%) for polio type 3, 84% (54–100%) for hepatitis A and 27% for hepatitis B (anti-HBs; 8–42%). Our results indicate insufficient protection against certain VPD in some subgroups. For all countries except Eritrea, measles seroprotection was below the 95% threshold required for elimination. Measles seroprevalence was lowest among adults younger than 25 years. In comparison, seroprevalence in the Dutch general population was 96% in 2006/07. The results of this study can help prioritizing vaccination of susceptible subgroups of adult asylum seekers, in general and in outbreak situations.